CONTEMPORARY TRENDS IN LEGAL CONVERGENCE - Asatryan, Armen (State and Law, 2022)
Convergence is one of the concepts of Western social science, which considers the tendency towards convergence of socio-political systems, overcoming economic, political and ideological differences between capitalism and socialism, with the goal of their further merging, to be a decisive feature of social development.The current stage in the development of legal knowledge suggests that many features of the development of legal systems cannot be adequately explained without introducing the concept of legal expansion, which is new for legal science.The means of legal convergence are expressed external legal and non-legal phenomena, through which the process of legal convergence is carried out, the achievement of convergence of law is ensured.In general, we can conclude that the forms of legal convergence and means are one of the central elements of the mechanism of legal convergence, the separation of means is expressed in the processes of legal convergence not only with the help of legal phenomena, but also with the help of non-legal (political, economic, etc.) ) phenomena and finally the observable elements are closely related to each other, interact with each other, for example, one of the forms of state activity through which legal convergence is carried out is legislative activity, i.e. legislative activity is at the same time a means of legal convergence, a guiding principle, expressing the essence of legal convergence.
Keywords: approximation of the legal system; legal convergence; law enforcement; systematization rights; legislative activity